ABOUT MEASURING VERTICAL FORCES IN FREIGHT CAR BOGIES - Manashkin, L. O.; Miamlin, S. V.; Pysmennyi, Ye. O. (Science and Transport Progress, 2004)
A method of compensation of longitudinal forces influence on the results of measurements of vertical forces in an axle-box and a side-frame interaction of the freight car three-piece bogie is presented in the paper.